KONSEP SMART LIVING PADA DESAIN INTERIOR RUANG TUNGGU PELANGGAN SEBAGAI INOVASI PERAWATAN BANGUNAN BENGKEL GAMA JAYA MOTOR - Ramadhani, Viola Malta; Nurmalasari, Riana (Narada : Jurnal Desain dan Seni, 2025)
Gama Jaya Motor is a car repair and maintenance workshop located in Surabaya. As a business entity, Gama Jaya Motor needs to manage its property to support its operations, one of which is building maintenance. In a workshop business, the customer waiting room is one of the most important aspects of property management, as it is directly used by customers. The interior of the customer waiting room should be designed to be attractive and aesthetically pleasing while maintaining customer comfort. This can be achieved by implementing an interior design concept based on smart living. This concept integrates various smart devices based on the Internet of Things (IoT) into the interior or building design, not only to enhance customer comfort but also to improve the operational efficiency of the workshop. This study employs a design-based case study method. The design process is carried out through field observations, interviews, and an analysis of spatial and technological requirements that can be integrated. The smart devices applied in the design include automatic lighting systems, CCTV, smart switches, smart sockets, and IoT-based temperature control systems. In addition to enhancing customer comfort, the implementation of the smart living concept is also expected to improve energy efficiency and the security of the workshop environment.